RISK FACTORS IN SEVERE ERECTILE DYSFUNCTION POPULATION - johanes, charles; Birowo, Ponco; Rasyid, Nur (Indonesian Journal of Urology, 2015)
Objective: To find the risk factors of severe erectile dysfunction. Material & methods: This Cross sectional study subjects completed the questionnare at the time of diagnosing Erectile Dysfunction (ED). Amount of 297 ED patients with mean age of 49.08 ± 13.69 years were enrolled consecutively at Urology Outpatient Clinic from 2005 to 2012. The questionnaire consisted of marital status, educational status, and occupation, comorbidities, habits, and International Index of Erectile Dysfunction-5 (IIEF-5) questionnare. We compared population proportion of ED severity (severe vs not severe) between sociodemographic, comorbidities and habits group and we also compared the mean of ED onset age and ED duration between those groups. Results: Of the patients, 29.3% were classified as severe ED, and 70.7% were classified other than severe ED (mild, mild-moderate, etc). The median of ED onset age was 47 years (46.64 ± 13.77 years) and the median of ED duration was 52 weeks (126.75 ± 167.69 weeks) ranged from 1 to 1040 weeks. We found status of low education level, unemployed, not married and having diabetes mellitus could increase the risk of having severe ED in ED population with each prevalence ratio was 1.44 (1.12-1.87), 2.02 (1.20-3.42), 1.91 (1.10-3.30), 2.01 (1.30-3.12). Not married group was also found have an earlier mean of ED age onset (mean difference 6.78 (2.37-11.19) years. Conclusion: We found that education level, occupation status, marital status and diabetes mellitus contributes in determining ED severity.